The environmental impact of medical waste: challenges and legal solutions - Brașoveanu, Florica (Technium Social Sciences Journal, 2023)
This paper analyses the impact of medical waste on the environment and identified the challenges and legal solutions for its management. Medical waste is a major global problem with significant environmental and public health impacts. The challenges of medical waste management, as well as the lack of adequate regulations, poor management practices and lack of awareness and education are problems that need to be addressed to improve environmental quality. An integrated legal framework, the creation of a reporting and monitoring system, the implementation of a system of extended producer responsibility, international collaboration and adequate financing of medical waste management should be considered in order to create an efficient and sustainable medical waste management system.